Evaluation of the efficacy and safety of nirmatrelvir/ritonavir co-administration inpatients with rheumatic disease infected with SARS-CoV-2: a real-world study - Zhong, Xue; Wang, Chao; Huang, Lin; Zhao, Yue; Li, Tianyi; He, Jing; Zhang, Xiaohong (Frontiers in Pharmacology, 2023)
The breakthrough development of novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccines and oral antivirals have played a critical role in curtailing the spread of the pandemic and dramatically reducing the morbidity and mortality rates among those infected. Among these oral antivirals, Nirmatrelvir/Ritonavir (NR) has been repurposed successfully for use against coronavirus disease-2019 and is now readily available on the market with promising therapeutic effects. Furthermore, certain patient subgroups, specifically those with rheumatic disease (RD) who are currently undergoing intensive immunodeficiency and/or immunosuppressive treatments, continue to be vulnerable and at a higher risk of experiencing severe consequences from COVID-19.Additionally, it has also been observed that NR exhibited prevalent drug-drug interactions of clinical significance, and more instances of COVID-19 rebound were being recognized with increasing frequency. Methods: A retrospective cohort study was conducted on a real-world RD population who were infected with SARS-CoV-2 and treated with NR. The time of symptoms resolution, length of hospitalization, and response rate were assessed. Results were compared among the different regimen groups. During the course, all grades adverse drug reactions (ADRs) directly associated with NR administration and associated with drug-drug interactions (DDIs) were also monitored.Results: A total of 32 patients with RD, who were infected with SARS-CoV-2 and withdrawal), one patient still experienced an increased International Normalized Ratio [INR,] and coagulation disorders (weak positive fecal occult blood test) on the second day after using NR. The INR levels decreased to nearly normal values, and coagulation disorders returned to normal after two days of discontinuing NR (the seventh day after the initial administration of NR).Conclusions: We showed NR therapy to be associated with a favorable outcome and an acceptable safety profile in an immunosuppressed population with RD during the Omicron surge. Early use of NR (within 5 days of symptom onset) could improve the prognosis of patients. NR administration for symptoms and confirmed SARS-CoV-2 infection after >5 days may also mitigate progression to severe disease, and is a viable strategy. Our results highlight the importance of utilization of early and/or NR indication, which may yield clinical advantages for patients with RD infected with SARS-CoV-2.